From agnosticism to theism / by Charles F. Dole, author of "The coming people, " "The theology of civilization, " "The religion of a gentleman, " etc. - Dole, Charles F. (Charles Fletcher), 1845-1927, author. (Tufts University. Tisch Library., 2016)
1 online resource (29 pages).; "Reprinted from the Hibbert journal."; Reproduction of the original from the Congregational Library & Archives.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Liberal series ;no. 1.